Ethical crowdfunding-led Islamic green finance - Al-Shaghdari, Fahd Mohammed Obad; Zakariyah, Habeebullah; Muhammad, Tijjani; Mohd Yusoff, Syarah Syahira (Routledge (Taylor & Francis Group), 2024)
The focal point of initiatives and undertakings directed towards environmental sustainability plays a crucial role in aligning the complex mutual relationships between society and the natural environment. In response to persistent environmental challenges over the past six decades, it becomes imperative to create favourable conditions for the initiation and extension of such initiatives into novel fields and geographical areas. Nevertheless, conventional funding mechanisms, including budget allocations and bank financing, are not frequently employed in support of environmentally conscious initiatives. Consequently, alternative financing avenues, with crowdfunding being particularly remarkable, have become extensively utilized in the realm of social and environmental projects. The main objective of this research is to analyse the symbiotic relationship between crowdfunding and green finance, scrutinizing the nuanced interaction that unfolds when financial accessibility converges with environmental stewardship. Through an in-depth examination of theoretical frameworks, recognizing a gap in the existing literature, this research undertakes a systematic literature review of relevant publications. Through this methodology, we seek to provide a nuanced understanding of the symbiotic relationship between crowdfunding and green finance. The main findings are that crowdfunding enhances green finance by enabling direct contributions to sustainable projects, ensuring transparency through blockchain, and bridging funding gaps in countries with limited institutional support. It also fosters innovation by supporting early-stage green tech start-ups, mobilizing resources for projects that may lack traditional funding. This study contributes to the literature by adding to the debate on the role of crowdfunding as an alternative source of funding for green projects.